Evaluation of intestinal histological damage in zebrafish exposed to environmentally relevant concentrations of manganese - Prado Rodrigues, Gabriela Zimmermann; Souza, Mateus Santos de; Silva, Antonia Homrich da; Zwetsch, Bruna Graziela; Gehlen, Günther (Ciência e Natura, 2018)
Manganese is an essential element for many physiological processes. However, in prolonged exposures or at high concentrations it may present toxicity to several organs, which has made it an object of study in pharmacological, behavioral, neurological and environmental research in different organisms. Thus, it was aimed to evaluate the damage caused by acute and chronic exposures to this element, through the histopathological analysis of the zebrafish (Danio rerio) intestine. Samples were embedded in paraffin for further processing in rotating microtome, and the slides were stained with Alcian Blue and hematoxylin for observation and analysis under light microscopy. The results demonstrate the ability of the metal to cause histological changes in this organ and to increase the secretion of mucus from globet cells in the region analyzed, mainly in the highest concentrations of Manganese Chloride. It is important to monitor the concentrations of this and other metals in the water bodies, given their toxicity.